Rusunami City Garden: Aspek Hukum Ketersediaan Air Bersih - Yuda, Ikbal; Suwandono, Agus; Pratiwi, Agus (Widya Yuridika, 2024)
This study aims to determine the implementation of the government's role in fulfilling clean water infrastructure at Rusunami City Garden Cengkareng in relation to the Consumer Protection Law and to determine the responsibility of the developer of Rusunami City Garden Cengkareng to consumers due to the non-fulfillment of clean water infrastructure reviewed based on the Consumer Protection Law. This study uses a normative juridical approach with descriptive analytical research specifications. The research was carried out using library research using primary, secondary, tertiary legal materials and field research using interviews and observations. The collected data will be analyzed using qualitative analysis methods. The results of this study are that the government does not play a role in the provision of clean water in the Cengkareng City Park Rusunami as evidenced by the existence of consumer problems. This is due to the shifting of authority between the central and regional governments so that the problem becomes protracted and the lack of oversight by the local government. Second, the developer's responsibility concerns public law and civil law. Public law is related to the state while data is related to consumers. Developers have met the elements of accountability for business actors regulated in Article 19 UUPK. Looking at the current needs where civil liability is the accountability most needed so as to facilitate accountability it is carried out by asking for criminal accountability first. Then followed by civil and administrative accountability.